The Influence of Corporate Governance and Corporate Social Responsibility on Financial Performance in ASEAN-5 - Eduard Ary Binsar Naibaho; Pande Saputra Nadeak (Universitas Pelita Harapan, 2025)
This study aims to analyze the influence of Corporate Governance and Corporate Social Responsibility on corporate financial performance in ASEAN-5, focusing on two performance indicators, namely Tobin's Q and Return on Assets (ROA). The method used was a regression analysis of panel data with secondary data from 144 companies listed on S&P Capital IQ during the period 2019 to 2023. This study employs the Fixed Effects research model for Model 1, while Model 2 utilizes the Random Effects model. The results of the study show that external corporate governance has no significant effect on financial performance, as measured by Tobin's Q. In contrast, debt financing has a negative impact on ROA's financial performance. In addition, market competition, as measured by the Herfindahl-Hirschman Index (HHI), did not affect Tobin's Q or ROA, while the ESG score showed no significant impact on either Tobin's Q or ROA. These findings offer valuable insights for companies to manage debt and develop sustainable strategies that enhance financial performance in a competitive market.